Eradication Therapy - Recent Trend in Research - Heung Up Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2020)
It is well known that Helicobacter pylori (H. pylori) can cause peptic ulcer, mucosa-associated lymphoid tissue lymphoma, atrophic gastritis, intestinal metaplasia, and ultimately, gastric cancer. Various studies have proven that H. pylori, which attaches to the gastric mucosa, is the cause of gastric cancer and can be eradicated using appropriate antibiotics. Since 2013, Japan has been carrying out national-led eradication treatment of H. pylori for the whole population. However, as drug exposure increases, the resistance rate to some antibiotics increases, and the pattern of antibiotic resistance varies from region to region. Therefore, the development of individualized antimicrobial therapies has become important since antibiotic resistance to H. pylori eradication is a problem worldwide. To help overcome this, remedies such as selection of antibiotics through susceptibility testing, selection of empirical treatment combinations appropriate for the region, dual therapy with high doses of amoxicillin, and the use of rifabutin or sitafloxacin with low antibiotic resistance have been studied. Potassium-competitive acid blocker has been reported to be more potent in inhibiting acid secretion than proton pump inhibitor, and its role in H. pylori eradication is expected. Drug formulations and regimens that are easy to take are being developed to increase compliance. New treatments such as spraying antibiotics directly to the gastric mucosa are being developed and studied.